Russian retail: expantion to the regions and the organizing changes (Путеводитель предпринимателя)
The relationship between the expantion to regions of Russian retail structures and their organizing changes is analysed. The region is considered as the set of businesses and also the principles of its operation. The new glance at the operation, development and transformation of the regional retail structures, systems and processes in them is considered in that context.